QUALITY OF EDUCATION IS A GUARANTEE OF OUR FUTURE ACHIEVEMENTS - Abdalova Sayyora Rustamovna; Quchkarov Sarvar Sattarovich (Galaxy International Interdisciplinary Research Journal, 2022)
This article discusses the large-scale positive work being done in the field of education, the main tasks of improving the quality and effectiveness of education.